Feasibility of using minimal incision in thyroidectomy operation - El Fol, Hossam Abdelkader; Ammar, Mohamed Sabry; Elbalshy, Mohammed A.; Sobeeh, Mohamed (International Surgery Journal, 2019)
Background: The conventional technique of thyroidectomy requires long skin incision, not satisfying patient and surgeon in terms of cosmesis and endoscopic thyroid surgery requires expertise. The aim of this study was to compare the clinical outcomes of patients undergoing minimal-incision thyroidectomy with those undergoing conventional thyroidectomy for benign thyroid diseases. Methods: Prospective randomized study that was carried on 50 patients who were undergone thyroidectomy at the department of surgery-Menoufia University from June 2018 to June 2019. The patients were divided into two groups. Group A included 25 patients who were operated upon using minimal incision thyroidectomy technique and group B included 25 patients who were undergone traditional thyroidectomy incision. Results: The length of skin incision was significantly shorter in the minimal-incision thyroidectomy than that in the conventional thyroidectomy group. Operative time was shorter in minimal incision technique. The incidence of postoperative complications was higher in conventional thyroidectomy group but didn’t reach to significant level. Patients undergone minimal-incision thyroidectomy experienced significantly less postoperative pain and were more satisfied with the cosmetic result than patients who underwent conventional thyroidectomy. Conclusions: Thyroid surgery can safely be performed as a minimally invasive procedure. Minimal access thyroid surgery is therefore a feasible and safe option for selected patients with excellent cosmetic outcome, with minimal learning curve.